2017
DOI: 10.1371/journal.pone.0177198
|View full text |Cite
|
Sign up to set email alerts
|

Tonic suppression of PCAT29 by the IL-6 signaling pathway in prostate cancer: Reversal by resveratrol

Abstract: Prostate cancer (PCa) is the second leading cause of cancer deaths in men. A better understanding of the molecular basis of prostate cancer proliferation and metastasis should enable development of more effective treatments. In this study we focused on the lncRNA, prostate cancer associated transcript 29 (PCAT29), a putative tumor suppressive gene. Our data show that the expression of PCAT29 was reduced in prostate cancer tumors compared to paired perinormal prostate tissues. We also observed substantially low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Prostate cancer associated transcript 29 (PCAT29), a tumor suppressor, is frequently overexpressed in prostate cancer and downregulated by interleukin (IL-6) in DU145 and LNCaP cells [ 51 ]. Significantly enhanced phopsphorylated-STAT3 has been observed following treatment with IL-6 (10 ng/mL) in DU145 and LNCaP cells [ 51 ]. STAT3 knockdown induced an increase in PCAT29 expression in both DU145 and LNCaP cells.…”
Section: Regulation Of Stat Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer associated transcript 29 (PCAT29), a tumor suppressor, is frequently overexpressed in prostate cancer and downregulated by interleukin (IL-6) in DU145 and LNCaP cells [ 51 ]. Significantly enhanced phopsphorylated-STAT3 has been observed following treatment with IL-6 (10 ng/mL) in DU145 and LNCaP cells [ 51 ]. STAT3 knockdown induced an increase in PCAT29 expression in both DU145 and LNCaP cells.…”
Section: Regulation Of Stat Signalingmentioning
confidence: 99%
“…Mechanistically, it was shown that STAT3 triggered the upregulation of miR-21, which consequently negatively regulated PCAT29 in PCa cells. Resveratrol repressed STAT signaling and stimulated expression of PCAT29 via repression of miR-21 [ 51 ] ( Figure 3 ). Further, protein inhibitor of activated STAT3 (PIAS3) has been found to be downregulated in medulloblastomas, and resveratrol shown to significantly upregulate PIAS3 in UW228-2, UW228-3, and DAOY cells with the repression of p-STAT3 levels [ 52 ].…”
Section: Regulation Of Stat Signalingmentioning
confidence: 99%
“…Another study [ 58 ] reported IL-6, a cytokine which is elevated in prostate tumours [ 59 ], reduced the expression of PCAT29 in both DU145 and LNCaP cell lines. IL-6 activates STAT3 which induces miR-21.…”
Section: Lncrnas Associated With Prostate Cancermentioning
confidence: 99%
“…This interaction leads to the repression of PCAT29. Inhibition of miR-21 was shown to increase PCAT29 expression [ 58 ].…”
Section: Lncrnas Associated With Prostate Cancermentioning
confidence: 99%
“…MALAT1 is a common lncRNA and has been noted to be up-regulated in renal carcinoma and is correlated with tumor progression and a poor prognosis by interacting with Ezh2 and miR-205 [22,23] . LncRNA PCAT29 is an androgen-regulated tumor suppressor initially identified in prostate cancer and has been recently proven to be related to hepatitis virus-related hepatocellular carcinoma [15,24] . In this study, we determined that PCAT29 was down-regulated in renal carcinoma and inhibited tumor growth by suppressing cell proliferation viability, invasion, and migration, revealing its antitumor role in renal carcinoma.…”
Section: Discussionmentioning
confidence: 99%